Analytical and Clinical Validation of the ConfiSign HIV Self-Test for Blood-Based HIV Screening - Hyeyoung Lee; Ae-Ran Choi; Hye-Sun Park; JoungOk Kim; Seo-A Park; Seungok Lee; Jaeeun Yoo; Ji Sang Yoon; Sang Il Kim; Yoon Hee Jun; Younjeong Kim; Yeon Jeong Jeong; et al. (Diagnostics)
Background/Objectives: Since the World Health Organization (WHO) recommended HIV self-testing as an alternative to traditional facility-based testing in 2016, it has been increasingly adopted worldwide. This study aimed to evaluate the performance of the ConfiSign HIV Self-Test (GenBody Inc., Republic of Korea), a newly developed blood-based immunochromatographic assay for the qualitative detection of total antibodies (IgG and IgM) against HIV-1/HIV-2. Methods: The evaluation included four components: (1) retrospective analysis of 1400 archived serum samples (400 HIV-positive and 1000 HIV-negative samples), (2) prospective self-testing by 335 participants (112 HIV-positive participants and 223 individuals with an unknown HIV status, including healthy volunteers), (3) assessment using seroconversion panels and diverse HIV subtypes, and (4) analytical specificity testing for cross-reactivity and interference. The Elecsys HIV combi PT and Alinity I HIV Ag/Ab Combo assays were used as reference assays. Results: In retrospective testing, the ConfiSign HIV Self-Test achieved a positive percent agreement (PPA) of 100%, a negative percent agreement (NPA) of 99.2%, and a Cohen’s kappa value of 0.986, showing excellent agreement with the reference assays. In the prospective study, the test showed 100% sensitivity and specificity, with a low invalid result rate of 1.8%. All HIV-positive samples, including those with low signal-to-cutoff (S/Co) values in the Alinity I assay, were correctly identified. The test also reliably detected early seroconversion samples and accurately identified a broad range of HIV-1 subtypes (A, B, C, D, F, G, CRF01_AE, CRF02_AG, and group O) as well as HIV-2. No cross-reactivity or interference was observed with samples that were positive for hepatitis viruses, cytomegalovirus, Epstein–Barr virus, varicella zoster virus, influenza, HTLV-1, HTLV-2, or malaria. Conclusions: The ConfiSign HIV Self-Test demonstrated excellent sensitivity, specificity, and robustness across diverse clinical samples, supporting its reliability and practicality as a self-testing option for HIV-1/2 antibody detection.